(untitled) (Research, Society and Development, 2024)
Introduction: Insomnia affects around 25% of the population and is the difficulty in starting to sleep, staying asleep or waking up earlier than desired, even when given adequate opportunity to sleep. Zolpidem is an imidazopyridine sedative-hypnotic, which acts as a positive allosteric potentiator of the alpha1 subunit of gamma-aminobutyric acid (GABA). It is approved to treat insomnia, increases the total duration of sleep stages and does not affect REM sleep. Objective: This study seeks to examine the main risks of zolpidem abuse and dependence in patients with insomnia. Materials and Methods: This is an integrative literature review on the main risks of zolpidem abuse and dependence in patients with insomnia. The PICO strategy was used to develop the guiding question. In addition, the descriptors "Zolpidem"; "Abuse"; "Dependence" were cross-referenced in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (VHL) databases. Results and Discussion: The risk of drug tolerance to zolpidem appears to be lower than to benzodiazepines, but abuse of the drug causes significant withdrawal effects, requiring specialized psychiatric management and follow-up, and is more common if there is a history of abuse and dependence. Conclusion: Prescribing high doses of zolpidem for chronic insomnia increases the risk of abuse and dependence. Therefore, it is recommended to avoid this indication whenever possible to prevent withdrawal symptoms. Prescription protocols need to be re-evaluated, prioritizing patient safety.